1805 Mass. Acts 111–13, ch. 81 - (:unkn) unknown (General Publisher, 1805)
Authorized the governor to appoint two provers per county who would prove musket and pistol barrels before sale. Proven barrels stamped. Violators fined ten dollars.
--
Keywords: MANUFACTURE ONLY